Helical assemblies of plasmonic nanorods as chiral metamaterials - A. Christofi; N. Stefanou; G. Gantzounis; N. Papanikolaou (Proceedings of SPIE, 2012)
We report on the optical properties of a layer-by-layer structure of silver nanorods, with their axes aligned perpendicular to the z direction and mutually twisted through an angle of 60° from layer to layer, by means of rigorous full electrodynamic calculations using the layer-multiple-scattering method, properly extended to describe axis-symmetric particles with arbitrary orientation. We analyze the complex photonic band structure of this crystal in conjunction with relevant polarization-resolved transmission spectra of finite slabs of it and explain the nature of the different eigenmodes of the electromagnetic field in the light of group theory. Our results reveal the existence of sizable polarization gaps and demonstrate the occurrence of strong optical activity and circular dichroism, combined with reduced dissipative losses, which make the proposed architecture potentially useful for practical applications as ultrathin circular polarizers and polarization rotators.